2018
DOI: 10.1093/brain/awy160
|View full text |Cite
|
Sign up to set email alerts
|

Intronic pentanucleotide TTTCA repeat insertion in the SAMD12 gene causes familial cortical myoclonic tremor with epilepsy type 1

Abstract: Familial cortical myoclonic tremor with epilepsy is an autosomal dominant neurodegenerative disease, characterized by cortical tremor and epileptic seizures. Although four subtypes (types 1-4) mapped on different chromosomes (8q24, 2p11.1-q12.2, 5p15.31-p15.1 and 3q26.32-3q28) have been reported, the causative gene has not yet been identified. Here, we report the genetic study in a cohort of 20 Chinese pedigrees with familial cortical myoclonic tremor with epilepsy. Linkage and haplotype analysis in 11 pedigre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
80
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 75 publications
(88 citation statements)
references
References 33 publications
8
80
0
Order By: Relevance
“…Long‐read sequencing might be another choice instead of southern blot analysis. Additionally, as pointed out previously , it was found that TTTCA insertions may, or may not, be accompanied by abnormal TTTTA expansions. In our patients, TTTTA expansions were not detected in family 3 holding the mutation in RAPGEF2 .…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Long‐read sequencing might be another choice instead of southern blot analysis. Additionally, as pointed out previously , it was found that TTTCA insertions may, or may not, be accompanied by abnormal TTTTA expansions. In our patients, TTTTA expansions were not detected in family 3 holding the mutation in RAPGEF2 .…”
Section: Discussionsupporting
confidence: 64%
“…The pentanucleotide repeats showed intergenerational instability and inversely correlated with age at onset of myoclonic tremor and epilepsy in our patient families, just as in spinocerebellar ataxia 31 (SCA31) . A founder effect between FCMTE1 pedigrees across China and Japan was indicated as a core haplotype containing the (TTTCA)n insertion was found to be shared among them . It should be noted that there is a chance that some repeat expansions could be missed by the current RP‐PCR strategy, e.g.…”
Section: Discussionmentioning
confidence: 67%
“…In this type of dynamic mutation, the complex repeat without the insertion is not pathological (Seixas et al, 2017). In addition to SCA37, this type of mutation underlies SCA31 (MIM# 117210) and benign adult familial myoclonic epilepsy (BAFME1; MIM# 601068, 6 and 7) (Cen et al, 2018;Ishiura et al, 2018;Sato et al, 2009;Seixas et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The pentanucleotide repeat associated with SCA37 is located in the middle poly-A of an AluJb element (Seixas et al, 2017). Several other disease-causing repeats are in middle or 3 ′ -end poly-A regions of Alu elements, such as the repeat expansions responsible for FRDA, DM2, and SCA10, as well as the pentanucleotide repeat insertions associated with SCA31 and two types of BAFME (Cen et al, 2018;Chauhan, Dash, Grover, Rajamani, & Mukerji, 2002;Clark et al, 2004;Ishiura et al, 2018;Kurosaki et al, 2012;Kurosaki, Matsuura, Ohno, & Ueda, 2009;Montermini et al, 1997;Sato et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This (TTTGA) n insertion was not detected using RP‐PCR or Sanger sequencing in 2 other FCMTE pedigrees without (TTTCA) n insertion. No (TTTGA) n insertion was detected in 238 Chinese controls using RP‐PCR or Sanger sequencing, although 24 controls with (TTTTA) n expansion were detected . Thus, similar to the previously reported (TTTCA) n insertion, the repeat expansion structure was speculated to be as follows: The (TTTGA) n insertion occurred between the (TTTTA) n expansion and its 3’ adjacent Alu element (Fig.…”
Section: Resultsmentioning
confidence: 97%